Are Current Shariah Governance Systems Efficient? - Kantakji, Mazhar Hallak; Zada, Najeeb; Alaeddin, Omar; Zainudin, Zalina (International Journal of Engineering and Technology, 2018)
This paper aims to examine the sufficiency of current Shariah governance systems with regards to both regulation and supervision. As compared to other factors, the importance of Shariah committee is a major part of the Shariah governance system and it requires a thorough assessment of its structure. The study finds that the main issues of the existing systems of Shariah governance are the absence of standardization and harmonization; lack of proper Shariah audit; the structure of the existing systems which rely solely on manpower; and the fact that a small number of Shariah scholars are controlling a vast number of Shariah committees.